Retinal microvascular and microstructural alterations in the diagnosis of dermatomyositis: a new approach - Huang, Bo-Zhi; Ling, Qian; Xu, San-Hua; Zou, Jie; Zang, Miao-Miao; Liao, Xu-Lin; Wei, Hong; Ying, Ping; Pei, Chong-Gang; Shao, Yi (Frontiers in Medicine, 2023)
Purpose: To study the relationship between fundus alterations, including retinal thickness and microvascular changes, and dermatomyositis (DM) using optical coherence tomography angiography (OCTA). Methods: A total of 16 patients with DM (32 eyes) and 16 healthy controls (HCs; 32 eyes) participated in this study. Based on the Early Treatment Diabetic Retinopathy Study subzones, OCTA fundus data was divided into different layers and regions for comparison. Results: The full retinal thickness (RT) in the inner nasal (IN), outer nasal (ON), inner inferior (II), and outer inferior (OI) regions of patients with DM was significantly lower than that of HCs (p<0.001). The inner layer RT was also significantly lower in the IN, ON, II, and OI regions in patients with DM (p<0.001).The outer layer RT was lower only in the II region in patients with DM compared to HCs (P<0.001). The full RT of the II region was more sensitive to the pathological changes of disease, since its ROC curve had an AUC of 0.9028, 95%CI: 0.8159-0.9898. Meanwhile, the superficial vessel density (SVD) of patients with DM was significantly lower in the IN, ON, II, and OI regions compared to HCs (p<0.001). The AUC for region II was 0.9634 (95%CI: 0.9034-1.0), which indicated good diagnostic sensitivity. Conclusion: OCTA can be used to evaluate relevant ocular lesions and monitor disease progression in patients with DM and interstitial lung disease.